Peran Serta Sekolah dan Guru Pada Murid Dalam Mengembangkan Program Makanan Jajanan Sekolah Yang Sehat - Marhaeni Fajar Kurniawati; Mariana Mariana; Elis Pebtianti; Ahmad Riduan; M. Rizhan Ridha (FKIP, Universitas Palangka Raya, 2024)
School snacks are foods that are usually sold at school and are known as snacks or snacks, lunches for students at school. Usually in the form of foods that are easy to carry and eat such as chips, candy or biscuits. School snacks can be snacks, drinks, ice cream or snacks that students can buy during break times or when they go home. School snacks are usually sold around or near the school, such as in the canteen, in nearby shops, or at snack outlets. School snacks need to be considered because they affect students' health and nutrition, and can affect their learning performance and behavior. Therefore, school snacks must be ensured to be quality and healthy. To ensure student health and academic success. Therefore, school snacks must be ensured to be high quality and healthy to ensure students' health, academic success and good behavior. Institutions have an important role in controlling snacks around schools. Institutions must make clear policies about permitted snacks, such as limiting oily, sweet, salty snacks, or foods with certain food additives. Schools must organize and select snack suppliers that meet quality and food safety standards. Schools must provide education about nutrition and health to ensure students understand the importance of healthy eating. Schools must provide healthy alternative foods such as fruit, vegetables or healthy biscuits for students.